Significant enhancement of Rashba spin–orbit interaction using metastable heavy metal interface - Taishiro Yamazaki; Sora Obinata; Riku Iimori; Kazumasa Yamada; Takashi Kimura (APL Materials)
Spin–orbit torque (SOT) is a fundamental phenomenon in spintronics, facilitating efficient control of magnetic states in advanced device architectures. The discovery of a large spin Hall angle in metastable heavy metals has significantly enhanced the potential of SOT-based devices. However, the inherently low electrical conductivity of these materials poses a critical obstacle to achieving efficient device performance. To overcome this limitation, we systematically investigate interfacial Rashba spin–orbit interactions at the interfaces between metastable heavy metals and highly conductive normal metals through a combination of theoretical and experimental approaches. First-principles calculations demonstrate that interfaces involving β-phase tungsten (β-W) and tantalum (β-Ta) exhibit substantially enhanced Rashba interactions compared to their α-phase counterparts. This enhancement is attributed to modifications in the interfacial electric field. Furthermore, we provide the first clear evidence of a positive correlation between the Rashba parameter and the interfacial work-function. These findings highlight the potential of engineering metastable interfacial structures to optimize spin–orbit coupling, enabling precise spin current control. This advancement offers a promising pathway for the development of high-performance spintronic devices and the realization of next-generation spin-based electronics.